Vibration mitigation in interlocking metasurfaces - O. Bolmin; P.J. Noell; N. Leathe; B.L. Boyce (Materials & Design)
Interlocking metasurfaces (ILMs) are a new class of mechanical metamaterials with patterned surface features that enable joining of two adjacent bodies, serving as an alternative to welds, fasteners, or adhesives. While the strength of ILMs has been explored previously, it is also possible to envision ILMs that possess the ability to dampen vibration or tailor energy transmission across the interface. In this study, we explore the vibration transmission under frequency sweep and random excitation of three ILM designs. This is the first study to characterize the response of ILMs under vibration. We find that ILMs which are tightly coupled (e.g., small interference fit) behave as a linear system and depart only marginally from the behavior of a solid body. However, through strategic manipulation of the ILM topology, and in particular the fit clearances, we show that vibrations can be damped by over an order of magnitude. Design strategies to employ ILMs for vibration mitigation are developed using a first-order model.